Natural Killer Cells Promote Kidney Graft Rejection Independently of Cyclosporine A Therapy - Ashraf, Muhammad Imtiaz; Sarwar, Attia; Kühl, Anja A.; Hunger, Elena; Sattler, Arne; Aigner, Felix; Regele, Heinz; Sauter, Martina; Klingel, Karin; Schneeberger, Stefan; Resch, Thomas; Kotsch, Katja (Frontiers in Immunology, 2019)
Natural Killer (NK) cells have recently been recognized as key players in antibody-mediated chronic allograft failure, thus requiring a comprehensive understanding whether NK cells can escape conventional immunosuppressive regimens. Influence of cyclosporine A (CyA) on NK cell function was studied in a mouse model of allogeneic kidney transplantation (KTX, BALB/c to C57BL/6). Recipients were treated daily with CyA (10 mg/kg) for seven or 14 days for long term survival (day 56). Administration of CyA in recipients resulted in significantly reduced frequencies of intragraft and splenic CD8+ T cells, whereas the latter illustrated reduced IFNγ production. In contrast, intragraft and splenic NK cell frequencies remained unaffected in CyA recipients and IFNγ production and degranulation of NK cells were not reduced as compared with controls. Depletion of NK cells in combination with CyA resulted in an improvement in kidney function until day 7 and prolonged graft survival until day 56 as compared to untreated controls. Surviving animals demonstrated higher intragraft frequencies of proliferating CD4+FoxP3+Ki67+ regulatory T (TREG) cells as well as higher frequencies of CD8+CD122+ TREG. We here demonstrate that NK cell depletion combined with CyA synergistically improves graft function and prolongs graft survival, suggesting that NK cell targeting constitutes a novel approach for improving KTX outcomes.